Highly Acid‐Resistant, Magnetically Steerable Acoustic Micromotors Prepared by Coating Gold Microrods with Fe3O4 Nanoparticles via pH Adjustment. (19th December 2016) - Li, Zeheng; Bai, Lanjun; Zhou, Chao; Yan, Xiaohui; Mair, Lamar; Zhang, Anning; Zhang, Li; Wang, Wei
Abstract : There is mounting interest in designing magnetically steerable nano‐ and micromotors for next generation medical nanorobotics, which requires biocompatibility for each individual component. Although various magnetic materials (e.g., Ni, Co, and Fe3 O4 ) have been incorporated into micromotors, their acid resistance remains largely unexplored. In this article, a simple one‐step method to prepare magnetic microrods via electrostatic attraction between paramagnetic magnetite nanoparticles (Fe3 O4 NPs) and gold microrods at appropriate pH values is reported. The as‐prepared Fe3 O4 ‐coated micromotors can be powered by MHz ultrasound and easily steered by external magnetic fields, and perform well in harsh working conditions such as high acidity, high viscosity, and high ionic strength. In particular, extended exposure to solution of pH as low as 0.9 has a minimal effect on the speed, steerability, or cargo‐transporting capability of micromotors coated with Fe3 O4 NPs, in stark contrast with those containing Ni segments. Considering the many challenges of biomedical applications, acid‐resistant, magnetically steerable Fe3 O4 ‐coated micromotors powered by MHz ultrasound can be a promising prototype for the future development of medical nano‐ and microrobotics. Abstract : Magnetically steerable, acid‐resistant micromotors can be simply fabricated by electrostatic attraction between magnetite nanoparticles and gold microrods at pH ≈ 4. These Fe3 O4 ‐coated microrods can be powered by ultrasound and controlled by magnetic fields, and resist acid degradation significantly better than Ni‐containing micromotors, and are therefore potentially useful for future biomedical applications.